Relationship of obesity and physical activity with academic performance among Indian dental students - Kuntamukkala, Jaya-Snehitha; Pentapati, Kalyana; Tadikonda, Abhinav N; Muliya, Vidya S; Mysore, Nanditha K; Tadikonda, Gautham K (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Dentistry curriculum is laborious, strenuous, and stressful and has little leisure time due to numerous academic activities. We aimed to evaluate the association of Academic Performance (AP) with physical activity (PA) and obesity. Methods: We performed a multicentric web-based survey through WhatsApp-based study groups among Indian dental students. A self-reported questionnaire that had information on age, sex, height, weight, current year, PA, and AP was used. PA was assessed using the International Physical Activity Questionnaire – short form which. is an open-ended 7-day recall questionnaire with 7 items (vigorous, moderate, walking, and sitting PA and the number of days, hours, and minutes spent on each activity). AP was recorded based on the average marks obtained in the previous academic year. Body Mass Index (BMI) was calculated by the formula weight (Kg)/ height (meters)2. Dental students who had not appeared in any of the examinations and were absent from the academic curriculum were excluded. Results: A total of 575 students were included out of which the majority were female (n=449). The majority of the participants had normal BMIs (59.1%) and were moderately physically active (n=246). Students with normal BMIs had higher mean AP scores than obese. Also, moderate and high PA students had higher mean AP scores than low PA students. Students with moderate and high PA had significantly higher estimates of AP when compared to low PA students after adjusting for year of study, BMI, and sex. Conclusions: PA has a positive association with AP among dental students.